What Happens to a Nursing Home Chain When Private Equity Takes Over? A Longitudinal Case Study - Aline Bos MSc; Charlene Harrington PhD (SAGE Publishing, 2017)
We analyzed what happens to a nursing home chain when private equity takes over, with regard to strategy, financial performance, and resident well-being. We conducted a longitudinal (2000-2012) case study of a large nursing home chain that triangulated qualitative and quantitative data from 5 different data sources. Results show that private equity owners continued and reinforced several strategies that were already put in place before the takeover, including a focus on keeping staffing levels low; the new owners added restructuring, rebranding, and investment strategies such as establishing new companies, where the nursing home chain served as an essential "launch customer."